PENGEMBANGAN MEDIA KOMIK DIGITAL PADA MATERI KEUNIKAN KEBIASAAN MASYARAKAT DI SEKITARKU MATA PELAJARAN IPAS KELAS IV SEKOLAH DASAR - Kadek Agus Dita Rismawan; I Made Sedana; Putu Yulia Angga Dewi (Widyajaya: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
The problem faced in IPAS learning is the minimal use of interactive learning media. The application of values and understanding of the traditions in the surrounding environment are also rarely implemented in the students' school environment. Therefore, creating learning media that connects values to everyday life becomes very important. This research aims to describe the design and analyze the validity and practicality of digital comic learning media on the topic of the uniqueness of community customs around me. This research uses the Research and Development (R&D) method with the ADDIE model, which includes the analysis, design, development, implementation, and evaluation stages, but is limited to the implementation stage. The research subjects consisted of 3 instrument experts, 6 product experts, and 3 teachers and 6 students from Grade IV of SD Negeri 1 Paket Agung, SD Negeri 1 Sari Mekar, and SD 2 Sari Mekar for practicality assessment. The data collection methods used include observation, interviews, documentation, and questionnaires. The research results show that digital comic learning media has very high validity, with scores of 0.9 from content experts, 0.9 from media experts, and 0.9 from language experts. At the practicality test stage, teachers gave a rating of 93% and students 94%, both of which fall into the very good category. This research concludes that digital comic learning media is highly valid and very practical for mathematics learning in elementary school.